Representasi Nilai-Nilai Budaya dalam Dulang Penamat Nyiwaq: Study pada Masyarakat Sukadana - Karmila Fatmawati; Muh. Khairul Hafizi; Ririn Desta Viana; Nanang Surya Jagat; M. Muzakkir Hifzi; Usuluddin Usuluddin (CV. Kalimasada Group, 2026)
The Dulang Penamat tradition is a form of local wisdom practiced by the Sasak community as part of the Nyiwaq funeral commemoration held on the ninth night after a person's death. Beyond its religious function, the tradition embodies cultural and social values that strengthen community cohesion amid social change. This study aims to analyze the cultural meaning, implementation process, social values, and preservation of the Dulang Penamat tradition in Sukadana Village, East Lombok Regency. A descriptive-interpretative qualitative approach was employed through observations, in-depth interviews, and documentation involving traditional leaders, religious leaders, bereaved families, and community members selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Dulang Penamat symbolizes the completion of the nine-day prayer sequence while serving as a medium for charity, gratitude, and social solidarity. The tradition reflects religious devotion, mutual cooperation, kinship, social responsibility, and respect for the deceased, while adapting to social changes without losing its essential cultural values. The study concludes that Dulang Penamat remains an important cultural mechanism for preserving Sasak identity and sustaining intangible cultural heritage across generations.